2023
DOI: 10.1021/acs.est.2c09682
|View full text |Cite
|
Sign up to set email alerts
|

Selenite-Catalyzed Reaction between Benzoquinone and Acetylacetone Deciphered the Enhanced Inhibition on Microcystis aeruginosa Growth

Abstract: The coexistence of selenite (Se(IV)) and acetylacetone (AA) generated a synergistic effect on the growth inhibition of a bloom-forming cyanobacterium, Microcystis aeruginosa. The mechanism behind this phenomenon is of great significance in the control of harmful algal blooms. To elucidate the role of Se(IV) in this effect, the reactions in ternary solutions composed of Se(IV), AA (or two other similar hydrogen donors), and quinones, especially benzoquinone (BQ), were investigated. The transformation kinetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…First, UV radiation alone has an impact on the physiological properties of algal cells . Several studies have demonstrated that UV radiation induces oxidative stress in cyanobacteria, leading to chemical modifications in their DNA and affecting their physiological activities. , Moreover, UV radiation has been shown to increase the specific gravity of algal cells and deactivate the algae. ,, In addition, AA also demonstrated an algicidal effect for freshwater cyanobacteria. AA inhibits cyanobacterial growth through a nonoxidative pathway by targeting nonheme iron in Photosystem II (PSII) and the iron–sulfur clusters in ferredoxin, selectively interfering with the photosynthetic electron transport chain in algal cells . Considering the effects of UV irradiation and AA molecules on the physiological activity of algal cells and the ability of the UV/AA system to degrade algae-related organic matter, a comprehensive investigation is warranted to understand the efficiency of UV-induced TXC coagulation (UV + TXC) in algae-laden water and the underlying enhanced mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…First, UV radiation alone has an impact on the physiological properties of algal cells . Several studies have demonstrated that UV radiation induces oxidative stress in cyanobacteria, leading to chemical modifications in their DNA and affecting their physiological activities. , Moreover, UV radiation has been shown to increase the specific gravity of algal cells and deactivate the algae. ,, In addition, AA also demonstrated an algicidal effect for freshwater cyanobacteria. AA inhibits cyanobacterial growth through a nonoxidative pathway by targeting nonheme iron in Photosystem II (PSII) and the iron–sulfur clusters in ferredoxin, selectively interfering with the photosynthetic electron transport chain in algal cells . Considering the effects of UV irradiation and AA molecules on the physiological activity of algal cells and the ability of the UV/AA system to degrade algae-related organic matter, a comprehensive investigation is warranted to understand the efficiency of UV-induced TXC coagulation (UV + TXC) in algae-laden water and the underlying enhanced mechanisms.…”
Section: Introductionmentioning
confidence: 99%